HIEMENZ STAGNATION POINT FLOW OF A TERNARY NANOFLUID AND HEAT TRANSFER DUE TO POROUS STRETCHING/SHRINKING SHEET WITH BRINKMAN MODEL - Vishalakshi, Angadi Basettappa; Vanitha, Gadabanahalli Puttasiddappa; Mahabaleshwar, Ulavathi Shettar; Botmart, Thongchai; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Begell House Inc, 2024)
The role of the Brinkman model is analyzed in the current work by taking the flow of ternary hybrid nanofluids with heat transfer in the presence of radiation and mass transpiration. The ordinary differential equations (ODEs) are yielded from the partial differential equations (PDEs) by using similarity variables. This flow is used in many real life significances viz., glass blowing, petroleum products, polymer extrusion, and so on. The role of the Brinkman model and radiation is used in velocity and heat equations. These equations are solved exactly to get a solution domain and confluent hypergeometric equation. Three types of nanoparticles, namely Al2O3, single wall carbon nanotubes, and graphene are inserted in the flow to enhance thermal efficiency. Additionally, dual behavior is seen in the instance of the shrinking sheet. Also, a unique solution is observed at the stretching sheet case. The novelty of the current analysis explains the stagnation point flow by considering the effect of the Brinkman model in the presence of ternary nanoparticles. By using these nanoparticles, the main goal of the current work is achieved. It includes the effect of the Brinkman model on ternary nanofluids, and the comparison between three nanoparticles can be achieved. The results of various parameters viz., solid volume fractions, mass transpiration, radiation, Brinkman number, porous medium parameter, and heat source/sink parameter can be examined with the help of graphical arrangements. At the end, we conclude the important outcomes as the solution domain value decays on rising values of porous medium parameter and mass transpiration values rise on increaing values of the solution domain.
Keywords: ternary nanofluid; radiation; porous medium; stretching/shrinking sheet; Brinkman model